2005
DOI: 10.1007/s00586-005-0975-6
|View full text |Cite
|
Sign up to set email alerts
|

Can povidone-iodine solution be used safely in a spinal surgery?

Abstract: Diluted povidone-iodine solution can be used safely in spinal surgeries, and it will not influence wound healing, bone union and clinical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
136
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(140 citation statements)
references
References 44 publications
1
136
0
3
Order By: Relevance
“…No patients had an adverse or allergic reaction [56]. Chang et al also conducted a prospective, randomized study on 244 adults undergoing PSF and found a 4.8% rate of deep SSI in the normal saline group, compared to no infections in the betadine group [55]. Similarly, Hardacker and Hardacker reported a significantly lower rate of deep SSI after adult PSF when dilute betadine irrigation was used (4% versus 0.7%) [57•].…”
Section: Irrigation Solutionsmentioning
confidence: 99%
“…No patients had an adverse or allergic reaction [56]. Chang et al also conducted a prospective, randomized study on 244 adults undergoing PSF and found a 4.8% rate of deep SSI in the normal saline group, compared to no infections in the betadine group [55]. Similarly, Hardacker and Hardacker reported a significantly lower rate of deep SSI after adult PSF when dilute betadine irrigation was used (4% versus 0.7%) [57•].…”
Section: Irrigation Solutionsmentioning
confidence: 99%
“…Therefore, syringe pressure irrigation of SC tissue with saline solution has been performed after colorectal surgery to decrease the incidence of postoperative wound infection. 25 In contrast, Chang et al 26 however, the authors concluded that intraperitoneal irrigation or wound irrigation with povidone-iodine may be useful in patients with dirty or contaminated wounds and in perforation or spillage during colorectal cancer operations. In questionnaires on intraoperative peritoneal lavage, 38% of surgeons used aqueous betadine in the case of the dirty abdomen.…”
Section: Discussionmentioning
confidence: 97%
“…In recently published CDC recommendations for SSI prevention, the use of aqueous iodophor solutions for intraoperative irrigation of deep or subcutaneous tissues is recommended [14]. The CDC based this recommendation on two randomised controlled trials performed in patients who underwent clean spine surgery [108,109] and on two randomised controlled trials performed in patients who underwent clean-contaminated, contaminated or dirty open abdominal surgery [110,111]. Again, it should be noted that these studies were not performed in musculoskeletal trauma patients, and specifically not in patients with an open fracture, where there is already serious damage to the local host environment.…”
Section: Surgical Debridement and Irrigationmentioning
confidence: 99%